Social and racial inequalities in diabetes and cancer in the United States - Massouh, Nour; Jaffa, Ayad A.; Tamim, Hani; Jaffa, Miran A. (Frontiers in Public Health, 2023)
Background: Cancer and diabetes are among the leading causes of morbidity and mortality worldwide.Several studies have reported diabetes as a risk factor for developing cancer, a relationship that may be explained by associated factors shared with both diseases such as age, sex, body weight, smoking, and alcohol consumption. Social factors referred to as social determinants of health (SDOH) were shown to be associated with the risk of developing cancer and diabetes. Despite that diabetes and social factors were identified as significant determinants of cancer, no studies examined their combined effect on the risk of developing cancer. In this study, we aim at filling this gap in the literature by triangulating the association between diabetes, indices of SDOH, and the risk of developing cancer.Methods: We have conducted a quantitative study using data from the Behavioral Risk Factor Surveillance System (BRFSS), whereby information was collected nationally from residents in the United States (US) with respect to their health-related risk behaviors, chronic health conditions, and the use of preventive services. Data analysis using weighted regressions was conducted on 389,158 study participants.Results: Our findings indicated that diabetes is a risk factor that increases the likelihood of cancer by 13% (OR 1.13; 95%CI: 1.05-1.21). People of White race had higher odds for cancer compared to African Americans (OR 0.44; 95%CI: 0.39-0.49), Asians (OR 0.27; 95%CI: 0.20-0.38), and other races (OR 0.56; 95%CI: 0.46-0.69). The indices of SDOH that were positively associated with having cancer encompassed unemployment (OR 1.78; 95%CI: 1.59-1.99), retirement (OR 1.54; 95%CI: 1.43-1.67), higher income levels with ORs ranging between 1.16-1.38, college education (OR 1.10; 95%CI:1.02-1.18), college graduates (OR 1.31; 95%CI: 1.21-1.40), and healthcare coverage (OR 1.44;). On the other hand, the indices of SDOH that were protective against having cancer were comprised of renting a home (OR 0.86; 95%CI: 0.79-0.93) and never married (OR 0.73; 95%CI: 0.65-0.81).This study offers a novel social dimension for the association between diabetes and cancer that could guide setting strategies for addressing social inequities in disease prevention and access to healthcare.